(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study uses postcolonial literary theory to analyze the processes of identity creation and socio-cultural ancestry in the Assamese novels Iyaruingom, Rongmilir Hahi, and Miri Jiyari. The paper assesses how cultural, linguistic, and ideological translation alters the depiction of marginalized people and their historical memory by placing the tales within larger contestations of language, culture, and power (Said 24). The study uses a multidisciplinary framework to show how the books both adapt to and reject prevailing cultural assumptions. The study also shows that translation in these works is not just linguistic but also civilizational, acting as a mediator between the demands of colonial and postcolonial modernity and indigenous worldviews (Bhabha 56). The novels highlight the relationship between individual identity and group belonging, showing how groups negotiate their position in socially transforming contexts. The lived sense of cultural hybridity and continuity is highlighted by this "translating the self" process. In the end, the study makes the case that these Assamese novels describe identity as a dynamic, changing construct that is influenced by memory, trauma, and negotiation with the prevailing discourse (Spivak 103). The study advances our knowledge of how postcolonial literatures retain, reconstruct, and reimagine socio-cultural heritage in the wake of historical disruptions by following these shifting identities.